2006
DOI: 10.1167/iovs.05-0380
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin B-Induced Mouse Model of Keratoconjunctivitis Sicca

Abstract: Intralacrimal gland injection of BTX-B resulted in persistent corneal fluorescein staining within 3 days, and a significant decrease in aqueous tear production that persisted for 1 month. Intralacrimal gland injection of BTX-B suppressed lacrimation, thereby establishing a dry eye state. This animal model could be a useful tool for investigating the pathogenesis of the chronic condition KCS in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 21 publications
4
41
1
1
Order By: Relevance
“…In addition, despite the long-term inhibition of the lacrimal gland tear production by BTX-B, the partial improvement of phenol-impregnated thread wetting in the medication treated groups could be explained by the compensatory response and the protection of the exorbital lacrimal gland from inflammatory damage. Although there was no evidence of inflammatory cells in histopathologic sections of the lacrimal glands and conjunctivae in the previous report of this model, 24 increased expression of various proinflammatory cytokines such as interleukin 1 has been shown in the lacrimal glands of the BTX-B-injected mice (unpublished data), which may explain the observed beneficial effects of FML and CsA. Accordingly, the responses to anti-inflammatory and immunosuppressive agents in this study may also support a role of inflammation in this dry eye mouse model.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…In addition, despite the long-term inhibition of the lacrimal gland tear production by BTX-B, the partial improvement of phenol-impregnated thread wetting in the medication treated groups could be explained by the compensatory response and the protection of the exorbital lacrimal gland from inflammatory damage. Although there was no evidence of inflammatory cells in histopathologic sections of the lacrimal glands and conjunctivae in the previous report of this model, 24 increased expression of various proinflammatory cytokines such as interleukin 1 has been shown in the lacrimal glands of the BTX-B-injected mice (unpublished data), which may explain the observed beneficial effects of FML and CsA. Accordingly, the responses to anti-inflammatory and immunosuppressive agents in this study may also support a role of inflammation in this dry eye mouse model.…”
Section: Discussioncontrasting
confidence: 50%
“…Therefore, the equivalent dose in a 20-g mouse would be 5 mU. From the previous study, 24 we showed that lacrimal gland injection of BTX-B resulted in ocular surface changes and significant reduction of tear production in as early as 3 days after injection. These effects lasted for at least 2 to 4 weeks.…”
Section: Mouse Dry Eye Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…After 3 min, the eye was flushed with artificial tears to remove excess fluorescein and examined using cobalt blue light from a slitlamp (PocketScope; Welch Allyn, Skaneateles Falls, NY). The degree of staining was scored based on the 0 -4 grading system (Lemp 1995;Nakamura et al 2005;Suwan-apichon et al 2006). A score of 0 indicated an absence of punctate fluorescein staining, a score of 1 indicated one-eighth or less of the corneal surface showed staining, a score of 2 indicated one-eighth to one-quarter of the corneal surface showed staining, a score of 3 indicated one-quarter to one-half of the corneal surface showed staining, and a score of 4 was given when greater than one-half of the corneal surface was stained.…”
Section: Methodsmentioning
confidence: 99%
“…Under direct visualization with an operating microscope, all mice received a transconjunctival injection of 0.05 mL of 20 mU of BTX-B solution into the left lacrimal gland, using a custommade 33-gauge needle, as described previously. 26 Three days after intralacrimal gland injection, each group received treatment with topical 100% HAF, 20% HS, or preservative-free artificial tears (control). Each treatment involved adding a 5-mL drop of the appropriate solution to the left eye 4 times daily for a 4-week trial period.…”
Section: Induction and Treatment Of Kcsmentioning
confidence: 99%